Allelopathic potential of aqueous leaf extract of Rumex dentatus L. on metabolites and enzyme activities of common purslane leaves. Issue 1 (31st December 2022) - El-Shora, Hamed M.; Alharbi, Maha M.; Darwish, Doaa B.; Gad, Dina
ABSTRACT: The present study was conducted to investigate the allelopathic activity of Rumex dentatus aqueous leaf extract on metabolites, reactive oxygen species (ROS), and enzymes activities in Portulaca oleraceae . The results showed a reduction of carbohydrates, protein, DNA, and RNA contents. However, the total phenolics, total flavonoids, and malondialdehyde were enhanced. The ROS such as hydrogen peroxide, superoxide radicals, and hydroxyl radicals were increased in concentration-dependent manner. The activities of glucose-6-phosphate dehydrogenase, 6-phosphoglucnate dehydrogenase, nitrate reductase, and glutamine synthetase were reduced in Portulaca leaves as the concentration of Rumex extract increased; however the activities of NADH-oxidase and phenylalanine ammonia-lyase were increased under treatment with the various tested concentrations of Rumex extract. Gas chromatography–mass spectrometry profile of aqueous Rumex extract was performed for the detection of the dominant compounds that may reveal the impact on Portulaca metabolites and enzymes activities.